Serum Vitamin D, Calcium and Phosphate among children with pneumonia - Oluwakeni Adegoke; Jerome Elusiyan; Joshua Owa; Perpetua Obianjuwa; Tewogbade Adedeji; Abimbola Phillips (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: Vitamin D is partly responsible for maintaining calcium and phosphate homeostasis but has been shown to have immune modulatory functions. Objective: To measure serum levels of vitamin D, and plasma levels of calcium and phosphate in children with pneumonia and compare with those of apparently healthy controls. Methods: A cross-sectional study involving seventy-six children with pneumonia, matched with 76 apparently healthy controls. Results: There was no statistically significant difference in the mean serum vitamin D levels between the cases and the controls (t = 1.190, p = 0.236). The mean serum vitamin D level was significantly higher in children with non-severe pneumonia than in those with severe pneumonia (t = 3.299, p = .002). The mean serum vitamin D level was higher among the controls than those with severe pneumonia (t = 2.674, p = 0.009). The mean plasma calcium and phosphate levels in the controls were significantly higher than in the cases (t = 2.528, p = .013 and t = 4.594, p < .001 respectively). Plasma calcium and phosphate levels did not vary with the severity of pneumonia. Pneumonia was independently associated with the occurrence of hypocalcaemia and hypophosphataemia (OR = 4.366, 95% CI = 1.851-10.295, p = 0.001; OR = 7.355, 95% CI = 1.545-35.027, p = 0.01 respectively). Conclusion: Children with severe pneumonia had lower levels of vitamin D than those with the non-severe disease. Derangements in plasma levels of calcium and phosphate are common in children with pneumonia, and these abnormalities occur independently of low vitamin D levels.